Spherical alpha-Al2O3 nanocrystal and preparation method thereof

Through PVP/SiO2 composite medium carrier and heat treatment technology, the agglomeration and impurities problems in the preparation of spherical α-Al2O3 nanograin are solved, and the preparation of nanograin with uniform morphology, narrow particle size and high purity is achieved, and the mechanics of the material is improved. and thermal stability.

CN119320153APending Publication Date: 2025-01-17HENAN JIYUAN BROTHER MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411446614.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare spherical α-Al2O3 nanocrystals with uniform morphology, which are prone to agglomeration and impurities introduction, resulting in uneven particle size distribution and low purity.

Method used

Using PVP/SiO2 composite medium carrier, through ultrasonic treatment and uniform precipitation reaction, uniform aluminum hydroxide crystal nuclei are formed, and the heating and cooling rate is controlled in high-temperature heat treatment to avoid excessive growth or rupture of grains, forming a uniform morphology. Spherical α-Al2O3 nanocrystals.

Benefits of technology

It significantly improves the morphology, particle size and purity of α-Al2O3 nanograins, improves mechanical properties and thermal stability, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to spherical alpha-Al2O3 nanocrystals and a preparation method thereof. The preparation method comprises the following steps: S1, preparing materials; the preparation method comprises the following steps: preparing a PVP / SiO2 composite medium carrier solution: dispersing nano silicon dioxide in deionized water, and uniformly dispersing the nano silicon dioxide through ultrasonic treatment; adding polyvinylpyrrolidone (PVP) into the obtained dispersion liquid, and stirring until the PVP is completely dissolved to obtain a PVP / SiO2 composite medium carrier solution; preparing an aluminum ion solution: taking high-purity inorganic aluminum salt as a precursor, and dissolving the aluminum salt in the PVP / SiO2 composite medium carrier solution to obtain the aluminum ion solution; step S2, precipitation reaction; s3, heat treatment; and S4, washing and drying are carried out, and the spherical alpha-Al2O3 nanocrystal grains are obtained. The preparation method has the advantages that uniform adsorption and hydrolysis reaction of aluminum ions are effectively guided through introduction of the PVP / SiO2 composite medium carrier, formation of spherical aluminum hydroxide precipitates is promoted, then the spherical aluminum hydroxide precipitates are converted into spherical alpha-Al2O3 nanocrystals with uniform morphology after high-temperature heat treatment, and the morphology, the particle size and the purity of the alpha-Al2O3 nanocrystals are effectively and remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of non-metallic oxides, in particular to spherical alpha-Al2O3 nano-crystals and a preparation method thereof. Background Art

[0002] As a high-tech inorganic material, alumina is widely used in ceramics, electronics, environmental protection and other fields. Alumina has eleven crystal forms, many isomorphous and heteromorphic, and mainly three crystal forms, namely α-alumina, β-alumina and γ-alumina. As the most stable crystal form, α-alumina occupies a very important position and a considerable proportion.

[0003] The methods for synthesizing α-Al2O3 powder include solid phase method, liquid phase method and gas phase method. The solid phase method is a method of directly obtaining nano-alumina by grinding and calcining aluminum or aluminum salt and causing solid phase reaction. However, the particle size distribution of the product prepared by it is uneven and easy to agglomerate; the liquid phase method is currently the most commonly used method for synthesizing nanoparticles, but it is easy to introduce impurities and the product purity is not high; the gas phase method product has less agglomeration, good dispersibility, small particle diameter, narrow distribution, but low yield and powder is not easy to collect. In summary, it can be seen that it is still difficult to prepare nano-α-Al2O3. The reason is that the particles of alumina will agglomerate during the crystal transformation process. High temperature calcination often leads to abnormal growth of grains and forms a worm-like structure, thus losing the advantage of the spherical morphology. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies in the prior art and provide spherical α-Al2O3 nanoparticles and a preparation method thereof. By introducing a PVP / SiO2 composite medium carrier, the uniform adsorption and hydrolysis reaction of aluminum ions are effectively guided, the formation of spherical aluminum hydroxide precipitates is promoted, and then after high-temperature heat treatment, the spherical α-Al2O3 nanoparticles are converted into spherical α-Al2O3 nanoparticles with uniform morphology, thereby effectively achieving a significant improvement in the morphology, particle size and purity of the α-Al2O3 nanoparticles.

[0005] The present invention is achieved through the following technical solutions: On the one hand, a method for preparing spherical α-Al2O3 nanoparticles is provided, which comprises the following steps:

[0006] Step S1, preparing materials;

[0007] Preparation of PVP / SiO2 composite medium carrier solution: disperse nano-silicon dioxide in deionized water and disperse it evenly by ultrasonic treatment; add polyvinyl pyrrolidone (PVP) to the obtained dispersion and stir until PVP is completely dissolved to obtain PVP / SiO2 composite medium carrier solution;

[0008] Preparation of aluminum ion solution: using high-purity inorganic aluminum salt as a precursor, and dissolving the aluminum salt in the PVP / SiO2 composite medium carrier solution to obtain an aluminum ion solution;

[0009] Step S2, precipitation reaction;

[0010] The precipitant is slowly added to the aluminum ion solution, and the solution is placed in a constant temperature reaction device after being stirred evenly. The precipitation reaction is carried out for 2-6 hours at a reaction temperature of 25-100°C and a pH value of 8-10, so that the aluminum ions are uniformly adsorbed on the surface of the PVP / SiO2 composite medium carrier and undergo a hydrolysis reaction to generate aluminum hydroxide (Al(OH)3) precipitate. The precipitate is uniformly adsorbed and grows on the surface of the PVP / SiO2 composite medium carrier to form a crystal nucleus, which further grows to form an intermediate.

[0011] Step S3, heat treatment;

[0012] In an inert gas environment, the intermediate is first pre-sintered at 600-900°C, then rapidly heated to 1100-1400°C, with the heating rate controlled at 5-20°C / min, then rapidly cooled to 1000-1100°C, with the cooling rate controlled at 5-20°C / min; and finally kept warm for 3-30h to obtain a crude α-Al2O3 nanoparticle.

[0013] Step S4: washing and drying to obtain spherical α-Al2O3 nanoparticles.

[0014] Through the above technical solution, the present invention disperses nano-silicon dioxide in a PVP solution to form a composite medium carrier; PVP, as a surfactant, can effectively improve the dispersibility of nanoparticles in water and prevent particle agglomeration, thereby ensuring that aluminum ions can be uniformly adsorbed on the SiO2 surface during the reaction. This uniform dispersibility is conducive to the subsequent hydrolysis reaction to generate uniformly distributed aluminum hydroxide (Al(OH)3) crystal nuclei, and ultimately promotes the formation of uniformly sized α-Al2O3 nanoparticles.

[0015] During the heat treatment process, the present invention adopts a process of pre-burning, rapid heating, and then rapid cooling, which can promote the effective conversion of intermediates, and controlling the heating rate and cooling rate helps to reduce thermal stress and avoid excessive growth or cracking of grains. Among them, the pre-burning process can remove organic matter and other impurities, rapid heating helps to promote the growth of grains and the improvement of crystallinity, and rapid cooling helps to fully crystallize and stabilize the grains, maintain the nanometer size and morphology of the grains, and then effectively achieve a significant improvement in the morphology, particle size and purity of α-Al2O3 nano-grains, and improve the mechanical properties, thermal stability and chemical stability of α-Al2O3 nano-grains.

[0016] Furthermore, in step S1, the mass ratio of the PVP to nano-SiO2 is 1:2-5.

[0017] Through the above technical solution, the polar groups on the PVP molecular chain interact with the surface of nano-SiO2 to form a PVP coating layer. This coating layer not only improves the dispersibility of nano-SiO2, but also provides a platform for the uniform adsorption of aluminum ions; the charge distribution on the PVP molecular chain and the surface charge of nano-SiO2 produce electrostatic interactions, further stabilizing the dispersion state of nano-SiO2; the protective layer formed by the PVP molecular chain on the surface of nano-SiO2 prevents the nanoparticles from approaching and agglomerating each other through the steric hindrance effect. Under the condition of a mass ratio of 1:2-5, PVP and nano-SiO2 can effectively regulate the growth direction and speed of the crystal based on the adjustment of factors such as the energy state and mass transfer rate during the crystal growth process, thereby optimizing the morphology and size of α-Al2O3 nanocrystals.

[0018] Furthermore, in step S1, the ultrasonic treatment time is 30-180 min, and the ultrasonic power is 20 KHz-50 KHz.

[0019] Through the above technical scheme, ultrasonic treatment utilizes the physical effects such as cavitation effect, micro jet and shock wave generated by high-frequency sound waves in liquid to strongly disperse and break up nano-silicon dioxide particles. With the extension of ultrasonic time and the increase of ultrasonic power, these physical effects become more significant, which helps to break the agglomeration and adsorption force between particles and make the nano-silicon dioxide particles more evenly dispersed in the solution. In addition, the ultrasonic treatment process helps to enhance the surface activity, adsorption capacity and reactivity of the composite medium carrier, thereby promoting the uniform adsorption of aluminum ions and the formation of aluminum hydroxide nuclei in the subsequent precipitation reaction, so as to achieve the purpose of promoting the formation of α-Al2O3 nano-crystals with uniform size and excellent performance.

[0020] Furthermore, in step S1, the inorganic aluminum salt is one or more of aluminum sulfate, boehmite or γ-Al2O3.

[0021] Through the above technical solution, aluminum sulfate dissolves in water and dissociates into Al 3+ and SO4 2- Ion, Al 3+ The adsorption of PVP / SiO2 composite medium surface forms a stable complex or adsorption layer. The presence of SiO2 reacts with Al 3+ Ions coordinate to further stabilize aluminum ions. As a high molecular polymer, PVP can coordinate with aluminum ions or SO4 through the functional groups on its chain. 2-The ions interact with each other, affecting the stability of the solution and the activity of aluminum ions. Boehmite undergoes hydrolysis or dissolution reaction in aqueous solution to generate Al 3+ Ions and OH - Ion (or H2O), Al 3+ The ions are adsorbed by the hydroxyl groups on the surface of SiO2 to form a stable aluminosilicate structure. PVP complexes with aluminum ions or hydroxide ions through the functional groups on its chain, further stabilizing the aluminum ions in the solution, thereby affecting the activity and distribution of aluminum ions. γ-Al2O3, as an oxide with a high specific surface area, is rich in hydroxyl groups and other active sites on its surface; when dissolved or dispersed in the PVP / SiO2 composite medium carrier solution, its high specific surface area and pore structure enable aluminum ions to be evenly distributed and stably present. The hydroxyl groups on the surface of γ-Al2O3 hydrogen bond or coordinate with the functional groups on the PVP chain, thereby enhancing the dispersibility and stability of γ-Al2O3 in the solution. SiO2 interacts with the hydroxyl groups on the surface of γ-Al2O3 through its surface hydroxyl groups to form a more complex oxide network structure, thereby improving the activity and uniformity of distribution of aluminum ions in the solution.

[0022] Further, in step S2, the stirring rate is 500-1000 rpm.

[0023] Further, in step S2, the precipitant is any one or more of ammonia water, urea, and sodium hydroxide. Preferably, the precipitant is ammonia water and urea; more preferably, the precipitant is ammonia water.

[0024] Furthermore, in step S3, a mineralizer is also included, and the mineralizer is a halogenated compound and / or a boron compound. Preferably, the halogenated compound is selected from any one of fluoride and chloride; the boron compound is boric acid; more preferably, it is a fluoride.

[0025] Furthermore, the added amount of the mineralizer accounts for 0.8-3.6% of the intermediate.

[0026] Through the above technical solution, the addition of mineralizer can reduce the energy required for alumina nucleation, promote the formation of a large number of crystal nuclei, and thus increase the specific surface area and active sites of the product. The addition of the above mineralizer can significantly reduce the sintering temperature and increase the specific surface area and sintering activity of spherical α-Al2O3 nanoparticles.

[0027] Furthermore, the method further comprises step S5, wherein the obtained spherical α-Al2O3 nano-particles are fully ground and dispersed by ball milling or air flow milling to obtain ultrafine spherical α-Al2O3 nano-particles.

[0028] Furthermore, the rotation speed of the ball mill in the ball milling process is 350-600 r / min, and the ball milling process time is 3-10 h.

[0029] Furthermore, in the air flow crushing method, the speed of the air flow crusher is 1200-2000 r / min, and the number of cyclic crushing times in the air flow crushing process is 1-10 times.

[0030] The size of the ultrafine spherical α-Al2O3 nanoparticles prepared under the above conditions is 25-70nm, and the specific surface area is 100m 2 / g-210m 2 / g.

[0031] Also provided is a spherical α-Al2O3 nano-crystal, which is prepared by the above-mentioned preparation method of the spherical α-Al2O3 nano-crystal.

[0032] Beneficial Effects

[0033] The polyvinyl pyrrolidone of the present invention is a surfactant, and the polar groups on its molecular chain can strongly interact with water molecules and the surface of nano-SiO2; this interaction forms a PVP coating layer on the surface of nano-SiO2, effectively reducing the surface energy of the nanoparticles, thereby reducing the mutual attraction between the particles. On the PVP / SiO2 composite medium carrier, aluminum ions can be uniformly adsorbed and undergo hydrolysis reactions to generate uniformly distributed Al(OH)3 crystal nuclei; under the joint action of PVP and SiO2, the crystal nuclei maintain a good dispersion state, avoiding agglomeration caused by excessive local concentration, thereby effectively solving the problem of easy agglomeration between spherical α-alumina particles, and effectively achieving a significant improvement in the morphology, particle size and purity of α-Al2O3 nanocrystals.

[0034] The present invention adopts a homogeneous precipitation method, and controls the slow addition of a precipitant and the temperature, pH value and other conditions of the reaction system, so that crystal nuclei are uniformly generated and grown in a PVP / SiO2 composite medium carrier, and adjusts the added mass ratio of PVP and nano-SiO2, combined with changes in the energy state and other factors during the crystal growth process, to effectively regulate the growth direction and speed of the crystal, thereby optimizing the morphology and size of α-Al2O3 nano-grains.

[0035] The present invention adopts high-purity inorganic aluminum salt as a precursor and performs heat treatment in an inert gas environment, thereby effectively avoiding the introduction of impurities and improving the purity of α-Al2O3 nano-grains.

[0036] The preparation method of the present invention is simple in process and easy to operate; the precipitation reaction conditions and the heating and cooling rates and the holding time during the heat treatment process are precisely controlled to achieve uniform distribution of the particle size of the α-Al2O3 nano-crystals, improve the uniformity of the product, and is particularly suitable for large-scale industrial production. In addition, adding an appropriate amount of mineralizer during the heat treatment effectively promotes the phase transition of the α-Al2O3 and reduces the phase transition temperature. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The experimental methods without specific conditions in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise specified, all percentages, ratios, proportions or parts are by weight.

[0039] Unless otherwise specified, the reagents and raw materials used in the examples and comparative examples of the present invention can be obtained through commercial channels.

[0040] Example 1

[0041] The method for preparing spherical α-Al2O3 nanoparticles comprises the following steps:

[0042] Step S1, preparing materials;

[0043] Preparation of PVP / SiO2 composite medium carrier solution: disperse nano-silicon dioxide in deionized water and disperse it evenly by ultrasonic treatment; add polyvinyl pyrrolidone (PVP) to the obtained dispersion and stir until PVP is completely dissolved to obtain PVP / SiO2 composite medium carrier solution; wherein the mass ratio of PVP to nano-SiO2 is 1:3, the ultrasonic treatment time is 90 min, and the ultrasonic power is 30 KHz;

[0044] Preparation of aluminum ion solution: high-purity aluminum sulfate is used as a precursor, and aluminum salt is dissolved in a PVP / SiO2 composite medium carrier solution to obtain an aluminum ion solution;

[0045] Step S2, precipitation reaction;

[0046] Slowly add ammonia water to the aluminum ion solution at a stirring rate of 800 rpm. After stirring evenly, place it in a constant temperature reaction device and carry out precipitation reaction for 4 hours at a reaction temperature of 80°C and a pH value of 9, so that the aluminum ions are uniformly adsorbed on the surface of the PVP / SiO2 composite medium carrier and undergo hydrolysis reaction to generate aluminum hydroxide (Al(OH)3) precipitate. The precipitate is uniformly adsorbed and grows on the surface of the PVP / SiO2 composite medium carrier to form a crystal nucleus, which further grows to form an intermediate.

[0047] Step S3, heat treatment;

[0048] In an inert gas environment, the intermediate was first pre-calcined at 800°C for 2 hours, then rapidly heated to 1250°C at a heating rate of 10°C / min, and then rapidly cooled to 1050°C at a cooling rate of 10°C / min; finally, the intermediate was kept at this temperature for 24 hours to obtain a crude α-Al2O3 nanoparticle.

[0049] Step S4: washing and drying to obtain spherical α-Al2O3 nanoparticles.

[0050] The average particle size of the spherical α-Al2O3 nanoparticles prepared under the above conditions is 50nm, and the particle size distribution is narrow; the purity is greater than 99.5%; the crystallinity is high, and the XRD spectrum shows a sharp α-Al2O3 characteristic peak; the spherical shape, smooth surface, and specific surface area of ​​100m 2 / g; high hardness, compressive strength> 200MPa; good thermal stability, maintaining structural stability at 1000℃.

[0051] Example 2

[0052] The method for preparing spherical α-Al2O3 nanoparticles comprises the following steps:

[0053] Step S1, preparing materials;

[0054] Preparation of PVP / SiO2 composite medium carrier solution: disperse nano-silicon dioxide in deionized water and disperse it evenly by ultrasonic treatment; add polyvinyl pyrrolidone (PVP) to the obtained dispersion and stir until PVP is completely dissolved to obtain PVP / SiO2 composite medium carrier solution; wherein the mass ratio of PVP to nano-SiO2 is 1:2, the ultrasonic treatment time is 120 min, and the ultrasonic power is 45 KHz;

[0055] Preparation of aluminum ion solution: high-purity aluminum sulfate is used as a precursor, and aluminum salt is dissolved in a PVP / SiO2 composite medium carrier solution to obtain an aluminum ion solution;

[0056] Step S2, precipitation reaction;

[0057] Slowly add ammonia water to the aluminum ion solution at a stirring rate of 800 rpm. After stirring evenly, place it in a constant temperature reaction device and carry out precipitation reaction for 4 hours at a reaction temperature of 80°C and a pH value of 9, so that the aluminum ions are uniformly adsorbed on the surface of the PVP / SiO2 composite medium carrier and undergo hydrolysis reaction to generate aluminum hydroxide (Al(OH)3) precipitate. The precipitate is uniformly adsorbed and grows on the surface of the PVP / SiO2 composite medium carrier to form a crystal nucleus, which further grows to form an intermediate.

[0058] Step S3, heat treatment;

[0059] In an inert gas environment, the intermediate was first pre-calcined at 800°C for 2 hours, then rapidly heated to 1400°C at a heating rate of 15°C / min, and then rapidly cooled to 1050°C at a cooling rate of 20°C / min; finally, the intermediate was kept at this temperature for 30 hours to obtain a crude α-Al2O3 nanoparticle.

[0060] Step S4: washing and drying to obtain spherical α-Al2O3 nanoparticles.

[0061] Compared with Example 1, the average particle size of the spherical α-Al2O3 nanoparticles prepared under the above conditions is 30-70nm, the particle size distribution is narrow, the purity is greater than 99.5%, the crystallinity is high, and the XRD spectrum (figure omitted) shows a sharp α-Al2O3 characteristic peak; the sphericity is good, the surface is smooth, and the specific surface area is 150m 2 / g; high hardness, compressive strength>250MPa; good thermal stability, maintaining structural stability at 1000℃.

[0062] Example 3

[0063] The method for preparing spherical α-Al2O3 nanoparticles comprises the following steps:

[0064] Step S1, preparing materials;

[0065] Preparation of PVP / SiO2 composite medium carrier solution: disperse nano-silicon dioxide in deionized water and disperse it evenly by ultrasonic treatment; add polyvinyl pyrrolidone (PVP) to the obtained dispersion and stir until PVP is completely dissolved to obtain PVP / SiO2 composite medium carrier solution; wherein the mass ratio of PVP to nano-SiO2 is 1:3, the ultrasonic treatment time is 120 min, and the ultrasonic power is 40 KHz;

[0066] Preparation of aluminum ion solution: high-purity aluminum sulfate is used as a precursor, and aluminum salt is dissolved in a PVP / SiO2 composite medium carrier solution to obtain an aluminum ion solution;

[0067] Step S2, precipitation reaction;

[0068] Slowly add urea to the aluminum ion solution at a stirring rate of 800 rpm. After stirring evenly, place it in a constant temperature reaction device and carry out precipitation reaction for 4 hours at a reaction temperature of 60°C and a pH value of 8.5, so that the aluminum ions are uniformly adsorbed on the surface of the PVP / SiO2 composite medium carrier and undergo hydrolysis reaction to generate aluminum hydroxide (Al(OH)3) precipitate. The precipitate is uniformly adsorbed and grows on the surface of the PVP / SiO2 composite medium carrier to form a crystal nucleus, which further grows to form an intermediate.

[0069] Step S3, heat treatment;

[0070] After adding 0.8% sodium fluoride solution to the intermediate and mixing evenly, the intermediate was first pre-calcined at 800°C for 2h in an inert gas environment, and then rapidly heated to 1250°C at a heating rate of 10°C / min, and then rapidly cooled to 1050°C at a cooling rate of 10°C / min; and finally kept warm for 24h to obtain a crude α-Al2O3 nanoparticle product;

[0071] Step S4: washing and drying to obtain spherical α-Al2O3 nanoparticles.

[0072] Compared with Example 1, the average particle size of the spherical α-Al2O3 nanoparticles prepared under the above conditions is 45nm, the particle size distribution is more uniform, the purity is greater than 99.5%, the crystallinity is higher, and the XRD spectrum shows a sharp α-Al2O3 characteristic peak; the sphericity is better, the surface is smoother, and the specific surface area is 110m 2 / g, with more surface active sites; high hardness, compressive strength>220MPa; good thermal stability, maintaining structural stability at 1000℃.

[0073] Example 4

[0074] The method for preparing spherical α-Al2O3 nanoparticles comprises the following steps:

[0075] Step S1, preparing materials;

[0076] Preparation of PVP / SiO2 composite medium carrier solution: disperse nano-silicon dioxide in deionized water and disperse it evenly by ultrasonic treatment; add polyvinyl pyrrolidone (PVP) to the obtained dispersion and stir until PVP is completely dissolved to obtain PVP / SiO2 composite medium carrier solution; wherein the mass ratio of PVP to nano-SiO2 is 1:3, the ultrasonic treatment time is 120 min, and the ultrasonic power is 40 KHz;

[0077] Preparation of aluminum ion solution: high-purity aluminum sulfate is used as a precursor, and aluminum salt is dissolved in a PVP / SiO2 composite medium carrier solution to obtain an aluminum ion solution;

[0078] Step S2, precipitation reaction;

[0079] Slowly add urea to the aluminum ion solution at a stirring rate of 800 rpm. After stirring evenly, place it in a constant temperature reaction device and carry out precipitation reaction for 4 hours at a reaction temperature of 60°C and a pH value of 8.5, so that the aluminum ions are uniformly adsorbed on the surface of the PVP / SiO2 composite medium carrier and undergo hydrolysis reaction to generate aluminum hydroxide (Al(OH)3) precipitate. The precipitate is uniformly adsorbed and grows on the surface of the PVP / SiO2 composite medium carrier to form a crystal nucleus, which further grows to form an intermediate.

[0080] Step S3, heat treatment;

[0081] After adding 0.8% sodium fluoride solution to the intermediate and mixing evenly, the intermediate was first pre-calcined at 800°C for 2h in an inert gas environment, and then rapidly heated to 1250°C at a heating rate of 10°C / min, and then rapidly cooled to 1050°C at a cooling rate of 10°C / min; and finally kept warm for 24h to obtain a crude α-Al2O3 nanoparticle product;

[0082] Step S4, washing and drying to obtain spherical α-Al2O3 nanoparticles;

[0083] Step S5, the obtained spherical α-Al2O3 nanoparticles are fully ground and dispersed by ball milling, the ball mill speed is 500r / min, the processing time is 5h, and ultrafine spherical α-Al2O3 nanoparticles are obtained.

[0084] Compared with Example 3, the average particle size of the spherical α-Al2O3 nanoparticles prepared under the above conditions is 30-40nm, and the particle size distribution is more uniform; the purity is greater than 99.5%; the crystallinity is reduced, and the XRD spectrum shows a sharp α-Al2O3 characteristic peak; the sphericity is good, and slight wear marks appear on the surface of some particles. The specific surface area is 150m 2 / g, more surface active sites; high hardness, compressive strength reduced to 180MPa; thermal stability slightly reduced.

[0085] Example 5

[0086] The method for preparing spherical α-Al2O3 nanoparticles comprises the following steps:

[0087] Step S1, preparing materials;

[0088] Preparation of PVP / SiO2 composite medium carrier solution: disperse nano-silicon dioxide in deionized water and disperse it evenly by ultrasonic treatment; add polyvinyl pyrrolidone (PVP) to the obtained dispersion and stir until PVP is completely dissolved to obtain PVP / SiO2 composite medium carrier solution; wherein the mass ratio of PVP to nano-SiO2 is 1:3, the ultrasonic treatment time is 120 min, and the ultrasonic power is 40 KHz;

[0089] Preparation of aluminum ion solution: high-purity aluminum sulfate is used as a precursor, and aluminum salt is dissolved in a PVP / SiO2 composite medium carrier solution to obtain an aluminum ion solution;

[0090] Step S2, precipitation reaction;

[0091] Slowly add urea to the aluminum ion solution at a stirring rate of 800 rpm. After stirring evenly, place it in a constant temperature reaction device and carry out precipitation reaction for 4 hours at a reaction temperature of 60°C and a pH value of 8.5, so that the aluminum ions are uniformly adsorbed on the surface of the PVP / SiO2 composite medium carrier and undergo hydrolysis reaction to generate aluminum hydroxide (Al(OH)3) precipitate. The precipitate is uniformly adsorbed and grows on the surface of the PVP / SiO2 composite medium carrier to form a crystal nucleus, which further grows to form an intermediate.

[0092] Step S3, heat treatment;

[0093] After adding 0.8% sodium fluoride solution to the intermediate and mixing evenly, the intermediate was first pre-calcined at 800°C for 2h in an inert gas environment, and then rapidly heated to 1250°C at a heating rate of 10°C / min, and then rapidly cooled to 1050°C at a cooling rate of 10°C / min; and finally kept warm for 24h to obtain a crude α-Al2O3 nanoparticle product;

[0094] Step S4, washing and drying to obtain spherical α-Al2O3 nanoparticles;

[0095] Step S5, using air flow pulverization method to fully grind and disperse the obtained spherical α-Al2O3 nanoparticles. The speed of the air flow pulverizer in the air flow pulverization method is 1800r / min, the air flow pressure is 8bar, and the number of cycles of pulverization in the air flow pulverization process is 5 times, so as to obtain ultrafine spherical α-Al2O3 nanoparticles.

[0096] Compared with Example 4, the average particle size of the spherical α-Al2O3 nanoparticles prepared under the above conditions is 25nm, the particle size distribution is more uniform, the purity is greater than 99.5%, the crystallinity is high, and the XRD spectrum shows a sharp α-Al2O3 characteristic peak; the sphericity is good, the surface is rough, and the specific surface area is 210m 2 / g, with many surface active sites; high hardness, compressive strength>210MPa; good thermal stability, maintaining structural stability at 1000℃.

[0097] Comparative Example 1

[0098] The method for preparing spherical α-Al2O3 nanoparticles comprises the following steps:

[0099] Step S1, preparing materials;

[0100] High-purity aluminum sulfate is used as a precursor and directly dissolved in deionized water to obtain an aluminum ion solution;

[0101] Step S2, precipitation reaction;

[0102] Ammonia water is slowly added to the aluminum ion solution at a stirring rate of 800 rpm. After stirring evenly, the solution is placed in a constant temperature reaction device and subjected to precipitation reaction for 4 hours at a reaction temperature of 80°C and a pH value of 9, so that the aluminum ions are uniformly adsorbed on the surface of the PVP / SiO2 composite medium carrier and undergo a hydrolysis reaction to generate aluminum hydroxide (Al(OH)3) precipitate. The precipitate grows naturally in the solution to form a crystal nucleus, which further grows to form an intermediate.

[0103] Step S3, heat treatment;

[0104] In an inert gas environment, the intermediate was first pre-calcined at 800°C for 2h, rapidly heated to 1200°C at a heating rate of 10°C / min, and then naturally cooled to room temperature to obtain a crude α-Al2O3 nanoparticle product;

[0105] Step S4: washing and drying to obtain spherical α-Al2O3 nanoparticles.

[0106] Compared with Example 3, the average particle size of the spherical α-Al2O3 nanoparticles prepared under the above conditions is larger, about 100-150nm, and the particle size distribution is wider; the purity is less than 99.5%, and contains a small amount of impurities; the crystallinity is lower, and the XRD spectrum shows that the characteristic peak of α-Al2O3 is not as sharp as that of Example 3; the sphericity is general, the surface is uneven, and the specific surface area is 80m 2 / g, which is relatively low; the hardness is lower than that of Example 3, and the compressive strength is greater than 180MPa; the thermal stability maintains structural stability at 1000°C, but the long-term high temperature stability is inferior to that of Example 3.

[0107] Comparative Example 2

[0108] The method for preparing spherical α-Al2O3 nanoparticles comprises the following steps:

[0109] Step S1, preparing materials;

[0110] High-purity aluminum sulfate is used as a precursor and directly dissolved in deionized water to obtain an aluminum ion solution;

[0111] Step S2, precipitation reaction;

[0112] Ammonia water is slowly added to the aluminum ion solution at a stirring rate of 800 rpm. After stirring evenly, the solution is placed in a constant temperature reaction device and subjected to precipitation reaction for 4 hours at a reaction temperature of 80°C and a pH value of 9, so that the aluminum ions are uniformly adsorbed on the surface of the PVP / SiO2 composite medium carrier and undergo a hydrolysis reaction to generate aluminum hydroxide (Al(OH)3) precipitate. The precipitate grows naturally in the solution to form a crystal nucleus, which further grows to form an intermediate.

[0113] Step S3, heat treatment;

[0114] In an air environment, the obtained intermediate is directly placed in a muffle furnace, heated to 1000°C at a relatively fast heating rate (e.g., 20°C / min), kept at this temperature for 2 hours, and then naturally cooled to room temperature;

[0115] Step S4: washing and drying to obtain spherical α-Al2O3 nanoparticles.

[0116] Compared with Example 3, the average particle size of the spherical α-Al2O3 nanoparticles prepared under the above conditions is larger and unevenly distributed, and agglomeration occurs; the purity is significantly reduced, and more oxide impurities are contained; the crystallinity is poor, the characteristic peak of α-Al2O3 in the XRD spectrum is not obvious, and there are multiple crystalline phases; the sphericity is poor, the surface is rough, and the specific surface area is low; the hardness and compressive strength are significantly reduced, the thermal stability is poor, and phase change occurs at high temperature.

[0117] In summary, compared with Comparative Example 1, the use of the PVP / SiO2 composite medium carrier in Examples 1 to 5 of the present invention provides a uniform nucleation environment for the hydrolysis reaction of aluminum ions, so that the generated aluminum hydroxide precipitate can be uniformly adsorbed on the surface of the carrier and grow into a sphere with a smooth surface; this morphology is not only beautiful, but also helps to improve the specific surface area and dispersibility of the material. Compared with Comparative Example 2, Examples 1 to 5 use precise heating and cooling rate control and a longer insulation time during the heat treatment process, which promotes the complete conversion of aluminum hydroxide to α-Al2O3 and improves the crystallinity of the crystal. This is demonstrated by the sharp α-Al2O3 characteristic peak in the XRD spectrum; among them, Example 2 successfully achieves the particle size control of nanocrystals through the mass ratio of PVP to nano-SiO2 and ultrasonic treatment conditions, with an average particle size between 30-70nm and a narrow particle size distribution. Heat treatment in an inert gas environment effectively avoids the introduction of impurities, making the purity of the final product higher than 99.5%; it also has a high specific surface area, high hardness and high compressive strength (>250MPa), and good thermal stability (maintains structural stability at 1000°C).

[0118] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing spherical α-Al2O3 nanoparticles, characterized in that: It includes the following steps: Step S1, preparing materials; Preparation of PVP / SiO2 composite medium carrier solution: disperse nano-silicon dioxide in deionized water and disperse it evenly by ultrasonic treatment; add polyvinyl pyrrolidone (PVP) to the obtained dispersion and stir until PVP is completely dissolved to obtain PVP / SiO2 composite medium carrier solution; Preparation of aluminum ion solution: using high-purity inorganic aluminum salt as a precursor, and dissolving the aluminum salt in the PVP / SiO2 composite medium carrier solution to obtain an aluminum ion solution; Step S2, precipitation reaction; The precipitant is slowly added to the aluminum ion solution, and the solution is placed in a constant temperature reaction device after being stirred evenly. The precipitation reaction is carried out for 2-6 hours at a reaction temperature of 25-100°C and a pH value of 8-10, so that the aluminum ions are uniformly adsorbed on the surface of the PVP / SiO2 composite medium carrier and undergo a hydrolysis reaction to generate aluminum hydroxide (Al(OH)3) precipitate. The precipitate is uniformly adsorbed on the surface of the PVP / SiO2 composite medium carrier and grows to form a crystal nucleus. The crystal nucleus further grows to form an intermediate. Step S3, heat treatment; In an inert gas environment, the intermediate is first pre-sintered at 600-900°C, then rapidly heated to 1100-1400°C, with the heating rate controlled at 5-20°C / min, then rapidly cooled to 1000-1100°C, with the cooling rate controlled at 5-20°C / min; and finally kept warm for 3-30h to obtain a crude α-Al2O3 nanoparticle. Step S4: washing and drying to obtain spherical α-Al2O3 nanoparticles.

2. The method for preparing spherical α-Al2O3 nanoparticles according to claim 1, characterized in that: In step S1, the mass ratio of PVP to nano-SiO2 is 1:2-5.

3. The method for preparing spherical α-Al2O3 nanoparticles according to claim 1, characterized in that: In step S1, the ultrasonic treatment time is 30-180 min, and the ultrasonic power is 20 KHz-50 KHz; the inorganic aluminum salt is one or more of aluminum sulfate, boehmite or γ-Al2O3.

4. The method for preparing spherical α-Al2O3 nanoparticles according to claim 1, characterized in that: In step S2, the stirring rate is 500-1000 rpm.

5. The method for preparing spherical α-Al2O3 nanoparticles according to claim 1, characterized in that: In step S2, the precipitant is any one or more of ammonia water, urea, and sodium hydroxide.

6. The method for preparing spherical α-Al2O3 nanoparticles according to claim 1, characterized in that: In step S3, a mineralizer is also included, and the mineralizer is a halogenated compound and / or a boron compound.

7. The method for preparing spherical α-Al2O3 nanoparticles according to claim 6, characterized in that: The amount of the mineralizer added is 0.8-3.6% of the intermediate.

8. The method for preparing spherical α-Al2O3 nanoparticles according to claim 1, characterized in that: The method further comprises step S5, wherein the obtained spherical α-Al2O3 nano-particles are fully ground and dispersed by ball milling or air flow crushing to obtain ultrafine spherical α-Al2O3 nano-particles.

9. The method for preparing spherical α-Al2O3 nanoparticles according to claim 8, characterized in that: The rotation speed of the ball mill in the ball milling process is 350-600 r / min, and the time of the ball milling process is 3-10 h.

10. The method for preparing spherical α-Al2O3 nanoparticles according to claim 8, characterized in that: The speed of the air flow pulverizer in the air flow pulverization process is 1200-2000 r / min, and the number of cyclic pulverization times in the air flow pulverization process is 1-10 times.

11. A spherical α-Al2O3 nanoparticle, characterized in that: The spherical α-Al2O3 nanoparticles are prepared by the preparation method of spherical α-Al2O3 nanoparticles described in any one of items 1-10.